Subjektivni pogledi poslancev na zakonodajo in nomotehniko - Igličar, Albin (Pravni letopis, 2009)
The only legislator in the Republic of Slovenia is the National Assembly of the Republic of Slovenia. From the quantity point of view its activity is quite comparalbe with the average number of acts passed by other parliaments, namely around 100. Yet the quality of the acts it has adopted is less satisying. Too many amending statutes and laws are adopted trough a necessary and summary procedure.The deputies themselves were self-critical in an evaluation they made trough a questionnaire at the end of the four-year mandate (2004-2008). From subjective and objective points of view, the main part of the Slovenian parliament's competence after 2004 relates to membership in the European Union. The deputies are involved in the European legislative procedure trough a special committee to which they send their statements. On the other side, a very big part of the legislature depends on the implementation of European directives in the Slovenian legal system.
Keywords: parlamenti; poslanci; Slovenia; Slovenija; zakonodaja; zakonodajni postopek